(untitled) (Research, Society and Development, 2020)
Air pollution and weather conditions are elements that can potentiate the transmission of viral infectious diseases. In this context, this article aims to analyze the influence of air quality and meteorological parameters on the transmission and deaths caused by COVID-19 in the metropolitan region of São Paulo during the period from March 17 to May 24 of 2020 year. For this purpose, meteorological and air quality data provided by the Environmental Company of the State of São Paulo (CETESB) were used, namely: ozone, coarse and fine particulate matter, carbon monoxide, nitrogen dioxide, nitrogen monoxide, nitrogen oxides, sulfur reduced, global solar radiation, relative air humidity, wind speed, atmospheric pressure, ultraviolet radiation and air temperature. A correlation analysis of these parameters was carried out (without and with a 5, 10, 15 and 20-day delay) with the confirmed cases and deaths by COVID-19 and a multiple regression model was used by the method of stepwise, remaining at the end, only the most significant predictors (at the 95% level). The results obtained showed that these predictors are: ozone, carbon monoxide, relative humidity, atmospheric pressure, ultraviolet radiation and air temperature. These variables explain 75% of the variability in cases and 76% of deaths from COVID-19. It can be concluded that meteorological factors, human and environmental health, are interconnected, and for this reason, it is important that measures to reduce air pollution are taken, which will contribute to a better quality of life for the population.